PENGEMBANGAN PERANGKAT PEMBELAJARANOPTIKA SMABERVISI SETS - Trisnaningsih, Tri Wijayanti (Universitas Negeri Semarang, 2011)
This research is a kind of developing research, which develops learning instruments visioned by SETS (Science, Environment, Technology, and Society). The main purpose of this research is to find out the improvement and learning result of physics subjects, especially in optical devices, of Xth grader students at SMA 1 Semarang. This purpose is held by implementing learning set/unit envisioned by SETS. This research is also held to know the impact of creativity in learning result. The subject for this reseach is class X.2 which consists of 39 students and is choosen randomly (cluster random sampling) from 9 regular classes exist. To understand the improvement of creativity and learning result of students, the writer makes some tests of verbal creativity and comprehension on the concepts of optical devices. The responds from the subject is known by giving a questionnaire about the learning process. Result of students creativity observed was 52% at the beginning and increase to 61% at the end. From the whole results of the learning process, the learning set/unit envisioned by SETS shows an improvement of learning result proved by increment of average value from 39 to 78 within the range of 0 â 100 so that 64% N-gain included in medium category.The lowest value before this process held was 19, and after this process held was 67. In addition, the highest value before this process held was 59, and after this process is held was 85. The influence of creativity to learning result of students is tested by analysis of simple regression, which tests normality of subject result in normal distribution. The value of R Square obtained in the research is 0.58. It means that students creativity influences the learning result by 58%. Meanwhile the rest of 42% (100%- 58%) was influenced by other factors which were not learnt in this study.